DYNAMIC INVENTORY MANAGEMENT IN THE ERA OF INDUSTRY HARNESSING AI AND ROBOTICS FOR AGILE OPERATIONS - Dwivedi, Seema; Singh, Chandan; Soni, Kartik; Tripathi, Shivam Kumar; Garg, Ankit Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today's Industry 4.0 landscape, dynamic inventory management stands as a cornerstone for businesses seeking to navigate the complexities of modern supply chains. Leveraging the transformative potential of Artificial Intelligence (AI) and Robotics, companies can revolutionize their inventory management strategies to achieve unprecedented levels of agility and responsiveness. AI algorithms enable precise demand forecasting, allowing organizations to optimize inventory levels in real time, thus mitigating the risks associated with stockouts or excess inventory. Concurrently, Robotics automation streamlines warehouse operations, enhancing efficiency while minimizing errors in inventory handling. By integrating AI and Robotics into their inventory management processes, businesses can adapt swiftly to fluctuating market demands, ensuring optimal resource allocation and fostering a competitive edge in today's dynamic business environment. However, amidst the promise of AI and Robotics, challenges persist. Issues such as data security, integration complexities, and workforce reskilling require careful consideration and strategic planning. Robust cybersecurity measures are essential to safeguard sensitive inventory data from potential breaches, while seamless system integration ensures smooth interoperability between AI-driven analytics platforms and Robotics automation systems. Furthermore, investing in comprehensive training programs is crucial to empower employees with the skills necessary to harness the full potential of these technologies. Overcoming these challenges is paramount for organizations aiming to unlock the full benefits of dynamic inventory management in the era of Industry 4.0, enabling them to thrive amidst rapid technological advancements and evolving market dynamics.